Development Strategy of Arabica Coffee in Conto Village, Bulukerto District, Wonogiri Regency - Wahyu Harinta, Yos; Fathul Anwar, Muhammad; Tutuko, Toyibatun (KnE Social Sciences, 2024)
This study aims to identify developing arabica coffee farming strategy in Conto Village, Bulukerto District, Wonogiri Regency. This study uses the descriptive analysis method to determine SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) to see internal factors, namely strengths and weaknesses, and external factors, namely opportunities and threats. The results showed that the analysis of the strategy owned by arabica coffee farming in Conto Village, Bulukerto District, Wonogiri Regency was in the position of cell or quadrant I (growth), which used incentive strategies including market penetration, market development, and product development. Alternative strategies for developing arabica coffee farming in Conto Village, Bulukerto District, Wonogiri Regency are the development of integrated coffee-based arabica coffee in each main area of arabica coffee production; the development of an arabica coffee agribusiness system on local resources and culture; the use of environmentally friendly and market-oriented technology, and the development of an arabica coffee agribusiness system directed at increasing the ability of farmers in cultivating coffee plants through increased counselling and demonstrating plot implementation. The priorities of the arabica coffee development strategy in Conto Village, Bulukerto District, Wonogiri Regency are as follows: increased counselling carried out by the government. Keywords: developing, coffee, strategy, farming